2022
DOI: 10.21203/rs.3.rs-2012413/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bioinformatics analysis of the primary molecular mechanism in lymphatic vascular space invasion and parametrial invasion of cervical cancer

Abstract: Purpose: Our study aims to investigate the underlying molecular mechanism between Lymphatic vascular space invasion (LVSI) and parametrial invasion (PMI) patients, and we screen biomarkers for patients with LVSI+ and PMI+.Methods: The main molecular mechanism of the LVSI+ and PMI+ groups was observed by using differential expression analysis and GO enrichment. Based on the results of Go enrichment, the distribution of immune infiltration was compared between the LVSI+ group and the PMI+ group by using ssGSEA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…A recent study by He et al also supports this observation; they found a suppression of adaptive immunity in LVSI+ patients. Their findings presented lower abundance of active CD4 T cells, natural killer T cells, effector memory CD8 T cell, and Treg in the LVSI+ group in comparison with the LVSI− group [18].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…A recent study by He et al also supports this observation; they found a suppression of adaptive immunity in LVSI+ patients. Their findings presented lower abundance of active CD4 T cells, natural killer T cells, effector memory CD8 T cell, and Treg in the LVSI+ group in comparison with the LVSI− group [18].…”
Section: Discussionmentioning
confidence: 91%
“…In particular, LVSI in CC is one of three Sedlis criteria-intermediate risk factors concerning early CC prognosis-along with a tumor size larger than 4 cm and deep stromal invasion [13][14][15][16][17]. As LVSI is an integral route that tumor cells disseminate, it guides physicians to inspect the possibility of local invasion and distant metastasis as well [18]. Furthermore, LVSI assists clinicians in surgical methods or patient management Life 2023, 13, 2342 2 of 16 decisions, such as paraaortic lymphadenectomy, adjuvant pelvic radiation, or aggressive chemotherapy [16,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation